THE EFFETCT OF FLOW VELOCITY AMONG TO THE PERFORMANCE OF PENGERIH FISHING GEAR - Heri primadi; Nofrizal '; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTPrimadi.heri@yahoo.comThe purpose of this study was to find the right position of fishing gear. If the goal was reached, this study is expected to provide benefits for fishermen in the field of arrest. The comparison of two arm and four arm straps were to determined the position of fishing gear on surface water. According to the period of fishing gear, the shift of fishing gear, the experimental results showed that the gear four arm straps on 49.6 cm / sec flow velocity, it can be said that fishing gear is better than two more stout rope arm movements.Keywords : Flow velocity, fishing gear performance, fishing gear